Cooling intervention and soccer under extreme heat conditions - Kurdak, S. S.; Özgünen, K. T.; Maughan, R.; Zeren, C.; Korkmaz, S.; Yazici, Z.; Ersöz, G.; Sirreffs, S.; Dvorak, J.; Binnet, M. S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Whole body pre-cooling with fluid ingestion had been discusses as one of the main interventions to improve athletic performance in extreme heat conditions. Extensive research had been performed to evaluate the effect of precooling on athletic performance and body core temperature, but the influence on a soccer match had not been investigated. Purpose: The aim of this study was to investigate the effect of cooling intervention on athletic performance and body core temperature during a competitive soccer game. Methods: 11 soccer players aged 21 ± 2 y (mean ± SD) with V`O2max of 59.8 ± 5.0 ml/kg/min volunteered to play two matches (without - C and with cooling intervention-CI) for this study. The ambient temperature and humidity was 34.3 ± 0.6 oC and 64 ± 2 % for the first and 34.0 ± 0.5°C and 62 ± 0 % for the second game (CI) respectively. Players had opportunity to consume ad libitum plain water during the C, plain water or sports drink by choice during CI study. A cooling tent and icy water filled buckets placed beside the soccer field were used for cooling intervention. Match activity was recorded by a global positioning system. Thermosensor pills were used for body core temperature (Tc) measurements. Blood samples were withdrawn from an antecubiteal vein 5 hours before and immediately after the game to determine hematocrit (Htc), hemoglobin content (Hb), calculate plasma volume loss, and changes of serum electrolytes. ANOVA and paired sample t-test was used to evaluate the level of significance, and p values < 0.05 were accepted as significant. . Results: The highest Tc value recorded during the last ten minutes of the first half and the difference between C and CI groups was not significant (39.54 ± 0.5 vs 39.3 ± 0.5oC respectively). Total liquid consumption was measured as 1473±422 ml for C, and 1230±494 ml for CI group (926±604 ml plain water, and 304±240 ml sports drink). Post-match dehydration % was similar for both C (2.49±0.67) and CI match (2.54±1.21). Pre- and post-match Htc (48.9±3.3 vs 49.2±3.3 %) and Hb (161±14 vs 163±13 g/L) were used to calculate % plasma volume change (0.1±5.5 %) for the C match. The plasma volume loss for the CI group was calculated as -5.1±5.6 with pre- and post-match Htc (46.2±2.3 vs 46.9±2.1) and Hb (153±10 vs 156±9) content. Plasma volume loss for C and CI groups were not significant. Pre- and postmatch difference of serum Na (145±2.5 vs 144±3 mmol/L), and K (5.4±0.4 vs 5.4±0.4 mmol/L) for C and CI groups were not significant. CI did not change distance covered during the game significantly (8298 ± 589 meters vs 8315±549 meters for C and CI groups respectively) Conclusion: Cooling intervention was not sufficient to reduce Tc and improve match performance significantly. Slight reduction of Tc that observed with whole body cooling, may be important for prevention of heath related problems that occur in extreme heat conditions.